If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-7z-6(5z+10)=8z
We move all terms to the left:
-7z-6(5z+10)-(8z)=0
We add all the numbers together, and all the variables
-15z-6(5z+10)=0
We multiply parentheses
-15z-30z-60=0
We add all the numbers together, and all the variables
-45z-60=0
We move all terms containing z to the left, all other terms to the right
-45z=60
z=60/-45
z=-1+1/3
| ∣4x+13∣=3x+16 | | -9(a-2)+15=42 | | m20=1 | | n+8=42;n+36 | | 4(1.5-k)-10=56/2 | | 8+6.95c=24.95 | | 7x/5-4=3 | | 4(p+19)-11=-7 | | X+2x+4-7=10 | | 106+11x-3=180 | | 2x^2+5x-20-4x=2x^2+2x | | v/3.2=1.9 | | 6x+39x-6=9 | | 6x+39x-6=9(5x+9) | | -2(x)=4x^2+3x-7 | | 12x-3=14x-17 | | P-1+9=3p-6 | | 3+32x+11x+5=180 | | 3x2-21=-6 | | 3+18+x=5x+6 | | -1.8=2(k+2.8) | | 9=11y-8y | | z/129/9=-27 | | 2.64(b+1)+1.16=6.44 | | 5(k-4+3k=4 | | 9+6/x=11 | | 3(f-11)-1=14 | | 8.3(x+3.1)=831 | | 4s+3-5=-6 | | 8-9=-10n | | 12^2x-8=1 | | -1+5c=-10+6c |